2008
DOI: 10.1007/s11661-008-9697-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Crevice Corrosion of Fe-Based Amorphous Metal and Crystalline Ni-Cr-Mo Alloy

Abstract: The crevice corrosion behaviors of an Fe-based bulk metallic glass alloy (SAM1651) and a Ni-Cr-Mo crystalline alloy (C-22) were studied in 4M NaCl solution at 100°C with cyclic potentiodynamic polarization and constant-potential tests. The corrosion damage morphologies, corrosion products, and the compositions of corroded surfaces of these two alloys were studied with optical three-dimensional reconstruction, scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), and Auger electron spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Fe 52 Mn 10 Mo 14 Cr 4 B 6 C 14 metallic glass is susceptible to pitting corrosion, although presents good corrosion resistance characterized by a low passivating current in 0.6 M NaCl solution [96]. Fe 48 Cr 15 Mo 14 B 6 C 15 Y 2 metallic glass, as known SAM1651, exhibits hysteresis loop during cyclic potentiodynamic polarization in 4 M NaCl solution at 373 K, which indicates the formation of localized corrosion [97]. Pardo et al [58,59] found that FeSiNbBCuCr metallic glass was immune to pitting corrosion in simulated industrial environments, since the current density decreased when the potential scan direction is reversed and it is identified that no pit formed on surface after immersion test.…”
Section: Pitting Corrosion Of Metallic Glassesmentioning
confidence: 99%
“…Fe 52 Mn 10 Mo 14 Cr 4 B 6 C 14 metallic glass is susceptible to pitting corrosion, although presents good corrosion resistance characterized by a low passivating current in 0.6 M NaCl solution [96]. Fe 48 Cr 15 Mo 14 B 6 C 15 Y 2 metallic glass, as known SAM1651, exhibits hysteresis loop during cyclic potentiodynamic polarization in 4 M NaCl solution at 373 K, which indicates the formation of localized corrosion [97]. Pardo et al [58,59] found that FeSiNbBCuCr metallic glass was immune to pitting corrosion in simulated industrial environments, since the current density decreased when the potential scan direction is reversed and it is identified that no pit formed on surface after immersion test.…”
Section: Pitting Corrosion Of Metallic Glassesmentioning
confidence: 99%
“…[1][2][3] Several Fe-based, exceptionally high corrosion-resistant structural amorphous metal compositions have been developed. [4][5][6][7][8][9][10][11][12][13][14][15] An Fe-based BMG material with a nominal composition of Fe 48 Cr 15 Mo 14 C 15 B 6 Y 2 (SAM 1651) was reported by J. Farmer et al to have high corrosion resistance in hot, concentrated calcium brine as well as in concentrated hydrochloric acid.…”
Section: Introductionmentioning
confidence: 99%
“…Farmer et al to have high corrosion resistance in hot, concentrated calcium brine as well as in concentrated hydrochloric acid. [4][5][6][7][8] Corrosion-resistant coatings cannot be achieved with thermally sprayed crystalline materials such as 316L stainless steels or Ni-based alloy 22 due to the segregation of undesirable phases, which leads to the loss of their corrosion resistance during the thermal spray process. However, thermal spray coatings of SAM 1651 retained their excellent corrosion-resistant performance as long as the amorphous structure is maintained.…”
Section: Introductionmentioning
confidence: 99%
“…The susceptibility of 316L stainless steel to crevice corrosion in a given environment may be assessed in a relatively short time using cyclic potentiodynamic polarization method [25,29,31]. Fig.…”
Section: Electrochemical Testsmentioning
confidence: 99%